Low-Molecular-Weight Chromium-Binding Substance (LMWCr) May Bind and Carry Cr(III) From the Endosome. (7th June 2021) - Edwards, Kyle; !Vincent, John
Abstract: Objectives: Transferrin, Tf, the protein that transports iron as Fe(III) from the blood to the tissues via endocytosis, is believed to also transport chromium(III), Cr(III). Under physiological conditions, Tf binds and releases Cr(III) rapidly; however, whether Cr(III) released from Tf in endosomes can be transported from the endosome before the endosome fuses with the cell membrane has been questioned. Cell culture studies have suggested a component(s) of the blood may be required for this Cr(III) transport, including potentially the metal-free form of oligopeptide low-molecular-weight chromium-binding substance, LMWCr. Methods: Human serum Cr(III)2 -Tf was prepared in a buffered solution at pH 7.4 (100 mM HEPES) containing 25 mM bicarbonate at 37 °C. LMWCr was isolated from bovine liver; Cr was removed from LMWCr by acidification in the presence of EDTA. To examine the release of Cr(III) from Cr(III)2 -Tf, the pH of solutions of Cr(III)2 -Tf and apoLMWCr were acidified from pH 7.4 to pH 5.5. After time intervals, aliquots were removed and frozen for analysis by electron paramagnetic resonance (EPR) spectroscopy, which can distinguish aquated Cr(III), Cr(III) bound to the two metal binding sites of Tf, and Cr(III) bound to LMWCr. Results: The acidification of solutions of Cr(III)2 -Tf and apoLMWCr in 100 mM HEPES and 25 mM bicarbonate solution, pH 7.4 to pH 5.5 resulted in a loss of Cr(III) from the N-terminal lobe of Tf with a t1/2 of 41 min, a ten-fold decrease from the t1/2 in the absence of apoLMWCr. Including simple chelating ligands such as citrate, ascorbate, or EDTA instead of apoLMWCr, only results in a 2-fold decrease. For loss of Cr(III) from the C-terminal lobe of Tf, inclusion of apoLMWCr resulted in a t1/2 of 1.8 minutes, a 3-fold decrease, while simple chelating ligands had no effect on the rate of Cr(III) loss. Released Cr(III) bound faster to apoLMWCr than to the chelating ligands. Conclusions: The results suggest apoLMWCr has a unique effect in accelerating the loss of Cr(III) from Cr(III)2 -Tf. LMWCr, which carries Cr(III) from the tissues to the urine for elimination from the body, may play a role in the removal of Cr(III) from Cr(III)-Tf and the transport of Cr(III) in endosomes into cells. Funding Sources: The University of Alabama Bioinorganic Chemistry of Chromium Research Fund.